Digital Art History as the Social History of Art: Towards the Disciplinary Relevance of Digital Methods. (3rd April 2019) - Jaskot, Paul B.
Abstract : Can we have a critical art history using digital methods? To answer this question, we need to ask what are the critical questions in art history that demand and are best suited to specific digital methods? This article argues that asking a critical question involves taking up the long art-historical tradition of the social history of art. Social art history is not satisfied with a social context for art, but rather reverses this equation by arguing that an analysis of art, artist, and audience must tell us something structurally about society. It is these kinds of questions that critically engage in broader art-historical debates. When questions such as these rely on large bodies of evidence – which they often do if "society" is their focus of study – then the scale of the project is, in today's context, best suited for digital methods. In sum, digital art history lets us address the tradition of the social history of art in new ways. The following essay seeks to advance a nuanced triangulation between our art-historical topics of study, our methodological debates, and computational analysis. In specific terms, exploring alternative subjects of art history as well as the particular analytical methods of social art history opens up the debates in the discipline to a more critical intervention with digital methods.